Sistem Pendukung Keputusan Pemilihan Paket Wedding Organizer Menggunakan Metode SAW (Simple Additive Weighting) - Rizka Ristiana; Yuwan Jumaryadi (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Preparing for a wedding is of course not easy, there is a lot to pay attention to so the event goes according to plan. There are several factors that must be considered, including the budget owned by the prospective bride and groom, because the budget decides what kind of concept the wedding organizer will give. There is a need for a system that can make it easier for customers to choose the wedding package that suits their wishes but does not take a long time. The SAW method is needed to find the weighted sum of the performance ratings for each alternative in all attributes. To provide recommendations for the desired package, there are several criteria. The criteria are calculated using the SAW method. The results of the ranking obtained V3 = 0.683 and V6 = 0.706. With the results of this ranking, it can be concluded that V6 is the alternative package chosen as the best alternative for service users with the weight of each criterion determined by the service user. What is expected from this research is the design results of the wedding organizer package selection used by customers in determining the best package as desired.